Agency of students participating in extracurricular activities and their interaction with parents in the context of the pandemic - Goshin, Mikhail; Grigoryev, Dmitry; Sorokin, Pavel; Bochkareva, Polina (Frontiers in Psychology, 2025)
This article investigates the relationships between strategies of parental involvement in education and manifestations of children’s agency during the pandemic seen as a potentially harmful and stressful context, requiring agency for sustaining well-being to a greater extent than before COVID-19. Data for the study were obtained through an online survey of students engaged in extracurricular activities, about the transition to distance learning and self-isolation during the pandemic. To elucidate the understanding of differences among respondents regarding changes in their interaction with parents, latent profile analysis was applied. It was found that joint activity between children and parents can be associated with the formation of a special type of agency, which is called ‘cooperative agency’, while parents providing children with freedom and facilitating support are associated with other behavioral characteristics of the child, i.e., ‘autonomous agency’. At the same time, the absence of interaction with parents, as well as parents’ display of strict control, do not contribute to successful adaptation to crisis conditions.